Jawapan

2016-03-02T22:16:15+08:00
Ni form brape punye soalan ni?
2016-03-05T00:50:45+08:00
2. g(x) = x+4/2x-5
let y = x+4/2x-5
y(2x-5)=x+4
2xy-5y=x+4
2xy-x=5y+4
x(2y-1)=5y+4
x=5y+4/2y-1
g-¹(x) = 5x+4/2x-1

g-¹(-3)
= 5x+4/2x-1
= 5(-3)+4/2(-3)-1
= -15+4/-6-1
= -11/-7
= 11/7

(3/11)(11/7)
=3
no1
x=-ax+b
let y = -ax+b
ax=b-y
x=b-y/a
f-¹x= b-x/a
ni jwpn no1
fx=-ax+b
let y = -ax+b
ax= b-y
x=b-y/a
f-¹x= b-x/a

f-¹7=4
4=b-7/a
4a=b-7
4a+7=B

f-¹(-3) =9
9=b-(-3)/a
9a=b+3
a=b+3/9

a=4a+7+3/9
9a=4a+10
9a-4a=10
5a=10
a=2

b=4a+7
b=4(2)+7
b=15

fx=-ax+b

let y = -ax+b

ax= b-y

x=b-y/a

f-¹x= b-x/a


f-¹7=4

4=b-7/a

4a=b-7

4a+7=B


f-¹(-3) =9

9=b-(-3)/a

9a=b+3

a=b+3/9


a=4a+7+3/9

9a=4a+10

9a-4a=10

5a=10

a=2


b=4a+7

b=4(2)+7

b=15